Majalah Fisika Berbasis Discovery: Pengembangan pada Materi Gaya dan Gravitasi Kelas X SMA/MA - Exia Anisa Sundari; Siti Aniatur Rofiqah; Widayanti Widayanti (Pendidikan Fisika Universitas Nurul Huda, 2023)
This research is a Research and Development development research that aims to develop physics magazine learning media and to determine the level of validity of physics magazine learning media and to determine the level of attractiveness of Discovery-based physics magazines in grade X students at the Senior High School (SMA) / Madrasah Aliyah (MA) level. This learning media development procedure uses a 4D model (Four-D Models) which consists of 4 stages of development and is focused on 3 development stage processes, namely define, design, develop. The location of the dissemination of the interesting questionnaire was carried out at MA Darussalamah Mudasentosa using a sample of 16 grade X students. The results showed that the Discovery-based physics magazine learning media on force and gravity material met the validation criteria by material experts with an average value of each assessment component of 0.70 and by media expert validators with an average value of each assessment component of 0.77, And student responses stated very interesting with an average score from each assessment component of 0.95